Evaluating the Factor Structure of the Posttraumatic Cognitions Inventory. (March 2022) - Whiteman, Sarah E.; Kramer, Lindsay B.; Silverstein, Madison W.; Witte, Tracy K.; Weathers, Frank W.
The Posttraumatic Cognitions Inventory (PTCI) is one of the most widely used measure of posttraumatic cognitions. The original factor analysis of the PTCI provided evidence for a three-factor model of negative cognitions about self, world, and self-blame. However, subsequent research has failed to replicate this factor structure without removing multiple items. Given these inconsistent findings, we examined the PTCI factor structure in a sample of trauma-exposed undergraduates ( n = 868). First, we conducted a series of four confirmatory factor analyses (CFAs) based on previously published models of the PTCI and a modified model based on previously removed items, all which indicated poor fit. Next, we conducted a CFA of the recently published three-factor PTCI-9, which approached adequate fit. We then replicated the CFA of the PTCI-9 in a second independent sample ( n = 971), finding a similar pattern of near adequate fit. These findings highlight the need to revise the PTCI. In addition, results indicate the promising nature of the PTCI-9 as an alternative measure of posttraumatic cognitions.